Prevalence of Toxoplasmosis in Pregnant Women - Aman Ullah, Yasmeen Bibi, Sajjad Mohammad, Fahad Ullah, Nighat Fatima, Syed Luqman Shuaib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Toxoplasmosis is a universal zoonotic disease approximately 30-50% of the individuals throughout the world have antibodies to Toxoplasma gondii. This study aimed to determine the prevalence of Toxoplasma gondii infection among pregnant women of Peshawar. Materials and Methods: The present cross-sectional study was conducted from September 2017 to December 2017. A total of 94 pregnant women attending antenatal care clinics were enrolled and screened for IgG and IgM antibodies against Toxoplasma gondii using the ICT technique. Results: Of the 94 pregnant women, 20 (21.3%) have either IgG or IgM antibodies detected against Toxoplasma gondii. Overall, positivity rate of IgG antibodies against Toxoplasma gondii was 14.9% while positivity rate of IgM antibodies was 6.3% in pregnant females. Highest sero-positivity was observed in elder age pregnant females with 8.51% in age age group 43-53 years. Conclusion: It is concluded that about one-fifth of the pregnant women in the present study were infected with Toxoplasma gondii parasites so the preventive method should be considered. Keywords: Toxoplasmosis, prevalence, pregnant women.